Outcome of 2 cc pure sulfur hexafluoride gas tamponade for macular hole surgery. Issue 1 (December 2016) - Kannan, Naresh; Adenuga, Olukorede; Kumar, Karthik; Ramasamy, Kim
Abstract Background Isoexpansile concentrations of intraocular gases are typically used as tamponading agent in macular hole surgery. Using a small volume of the pure form of these gases may achieve the same result without increasing the incidence of postoperative complications. The purpose of this study was to evaluate the anatomical and visual outcomes following macular hole surgery with 2 cc pure (100 %) sulfur hexafluoride (SF6 ) gas tamponade. Methods A retrospective study of eyes with idiopathic macular holes that underwent 23-gauge pars plana vitrectomy with 2 cc pure SF6 gas tamponade. Macular hole surgery was performed alone or in combination with phacoemulsification in eyes with cataract. Preoperative and postoperative data including best corrected visual acuity recorded in LogMAR units, slit-lamp biomicroscopy, and optical coherence tomography were analysed. Surgical complications were also recorded. Results Seventy six eyes of seventy five patients were analysed. A closure rate of 100 % was achieved with reoperation in 4 eyes. There was a significant improvement in best-corrected visual acuity from a mean of 0.65 LogMAR preoperatively to 0.36 at 6 months (p value 0.004). Forty five (59 %) eyes gained at least 2 lines on the Snellen visual acuity chart. Postoperative elevation in intraocular pressure (≥30 mmHg) was documented in 3 eyes (4 %). Conclusion Macular hole surgery with 2 cc pure SF6 gas tamponade achieved a high success rate with a low incidence of complications. The smaller volume of gas required makes it a cheaper technique.